2021
DOI: 10.3390/ijms222111954
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Structural Dynamics of the Activation Gate of KcsA Using Homo-FRET Measurements

Abstract: The allosteric coupling between activation and inactivation processes is a common feature observed in K+ channels. Particularly, in the prokaryotic KcsA channel the K+ conduction process is controlled by the inner gate, which is activated by acidic pH, and by the selectivity filter (SF) or outer gate, which can adopt non-conductive or conductive states. In a previous study, a single tryptophan mutant channel (W67 KcsA) enabled us to investigate the SF dynamics using time-resolved homo-Förster Resonance Energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…To label the proteins with dye, a 1:1 mixture of sulfo-Cy3 maleimide (Lumiprobe) and sulfo-Cy5 maleimide (Lumiprobe) was added to the proteins at a protein:fluorophore molar ratio of 1:10. The labeling reaction was performed at 4 °C for 2 h. The labeled proteins were then diluted and added to anti-FLAG resin, and the excess free dyes were effectively removed by extensive washing 29 . The proteins were eluted by elution buffer and concentrated to 0.3–0.4 mg ml −1 (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To label the proteins with dye, a 1:1 mixture of sulfo-Cy3 maleimide (Lumiprobe) and sulfo-Cy5 maleimide (Lumiprobe) was added to the proteins at a protein:fluorophore molar ratio of 1:10. The labeling reaction was performed at 4 °C for 2 h. The labeled proteins were then diluted and added to anti-FLAG resin, and the excess free dyes were effectively removed by extensive washing 29 . The proteins were eluted by elution buffer and concentrated to 0.3–0.4 mg ml −1 (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in the KcsA channel have shown that the fluorescence emitted by W67, located at the pore helix, nicely reports on cation occupancy-induced conformational changes in the nearby SF [ 25 , 26 , 37 ]. Furthermore, the occurrence of a homo-FRET process among the W67 residues present in the four KcsA channel subunits allowed for the calculation of intersubunit distances under different ionic conditions through the analysis of both steady-state and time-resolved fluorescence anisotropy [ 25 ].…”
Section: Resultsmentioning
confidence: 82%
“…KcsA is among the best studied channels by X-ray crystallography, yet among more than 100 structures deposited to the Protein Data Bank, there is not a single structure of the open wild-type protein. Other methods, such as EPR or SANS appear to detect structural changes at low pH [63][64][65] . As none of the deposited structures are solved below pH of 4.0, the pH at which the HBC in KcsA was suggested to open, it might be that the open conformation of KcsA displays substantial heterogeneity which precludes crystallization.…”
Section: Discussionmentioning
confidence: 99%